Suspected Radial Head Subluxation in Infants: The Need for Radiologic Evaluation. Issue 1 (January 2021) - Hanes, Lauren; McLaughlin, Robyn; Ornstein, Amy E.
Abstract : Abstract: Radial head subluxation ("pulled elbow" or "nursemaid's elbow") is a common pediatric condition in children aged 1 to 4 years, although it is an uncommon finding in nonambulatory infants. It is a clinical diagnosis, and further investigations such as x-ray are not routinely done. We present a case series of 2 nonambulatory infants with forearm fractures that were initially diagnosed as radial head subluxation. Current literature supports the use of x-ray in children with atypical or unclear history prior to an attempted pulled elbow reduction. We suggest that this recommendation should be extended to all nonambulatory infants, given the unlikely diagnosis of radial head subluxation, and the necessity for early recognition of injuries that may be indicators of abuse.